Pelaksanaan Supervisi Pendidikan Untuk Meningkatkan Profesionalitas Guru di TK Assalam Karawang - Syifa Farihatun Afifah,; Karyawati, Lilis; Karnia, Nia (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
This study was motivated by the results of observations that researchers made of teachers at Assalam Kindergarten. The problem in this study is that there are signs of poor teacher competence, especially in newly recruited teachers. Usually they do not have interaction skills with students and do not master what the principles are in the classroom teaching and learning process. The purpose of this research is to find out and explain about educational supervision activities to support teacher competence at Assalam Kindergarten. The research method used is a qualitative method with a phenomenological approach to understand individual experiences and perceptions related to the phenomenon under study. Data obtained through interviews, observation and documentation. The results of the research conducted indicate that the supervision program carried out periodically by the principal is proven to be able to improve the professionalism of Assalam Kindergarten teachers.